ANALISIS PENGGUNAAN TEKNOLOGI DALAM PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA DI SMK NEGERI 2 TOMA - Arifin Gaho (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2023)
The research aims to analyze the use of technology in learning on students' interest in learning at SMK Negeri 2 Toma. This research was designed using a qualitative approach method. This research was discovered through observation, documentation and interview data collection techniques with teachers and students. The data analysis techniques used are data reduction, data presentation, and drawing conclusions and verification. Based on the research results that the researchers found, the researchers concluded that the use of technology used at SMK Negeri 2 Toma, namely computers, laptops and WiFi networks, functions as a tool in the learning process, and this has increased students' interest in learning. Judging from the students' interest in using technology in learning at SMK Negeri 2 Toma, it is very good, where students at SMK Negeri 2 Toma really like or are interested in using technology in learning. The suggestions put forward by researchers are: 1) All teachers should use technology in the form of computers, laptops and WiFi networks in learning at SMK Negeri 2 Toma, because their use can increase students' interest in learning. 2) The use of technology in learning at SMK Negeri 2 Toma should be further increased.